Reconstructing Tascalusa's chiefdom : pottery styles and the social composition of Late Mississippian communities along the Alabama River - Regnier, Amanda Leigh (The University Alabama Press, 2014)
"Reconstructing Tascalusa's Chiefdom is an archaeological study of political collapse in the Alabama River Valley following the Hernando de Soto expedition. To explain the cultural and political disruptions caused by Hernando de Soto's exploration deep into North America, Amanda L. Regnier presents an analysis of ceramics and a novel theory of cultural exchange, which argues that culture consists of a series of interconnected models governing proper behavior that are shared across the belief systems of communities and individuals. An approach not often applied to archaeological research, ceramic study serves as a test of whether historic cognitive models can be extracted from ceramic data via cluster and correspondence analysis. In addition, the summary of Late Mississippian sites includes a chronology of the Alabama River from approximately AD 900 to 1600, which previously has only existed in manuscript form, and a summary of excavations at major Late Mississippian sites along the Alabama River. The results of the study demonstrate that the Alabama River Valley was settled by populations migrating from three different geographic regions during the late fifteenth century. The mixture of ceramic models associated with all three traditions at Late Mississippian sites suggests that these newly founded towns had a distinct mix of ethnically and linguistically diverse populations. Based on the archaeological record, the polity controlled by Tascalusa appears to have been both multiethnic and newly formed. Perhaps most significantly, Tascalusa's chiefdom appears to be a pre-contact example of a coalescent society that emerged after populations migrated into a new region from the deteriorating Mississippian chiefdoms in their homelands"--